Drug utilization review of intravenous proton pump inhibitors in a tertiary government hospital - Arevalo, Czarina Franz B.​; Salazar, Lyka Rica S.​; Tayko, Erica Nicole J.​
Proton pump inhibitors (PPIs) are indicated as management for various gastrointestinal related diseases, Zollinger-Ellison Syndrome, and prophylaxis for stress-induced ulcers. However, studies have shown that intravenous PPIs (IV PPIs) are inappropriately prescribed and irrationally used in hospitals which entails higher healthcare costs and exposure to risks of potential adverse effects. Therefore, this study aimed to determine the patterns of IV PPI in a tertiary government hospital and to determine drug-related therapy problems and their financial implications. Through purposive sampling, a retrospective review of patient medical charts was employed. Only patients with prescribed IV PPIs, male or non-pregnant female patients aged 18 years old or older, admitted or transferred to the Internal Medicine wards within January 1 to March 31, 2018 were included in the study. Results showed that omeprazole was the sole IV PPI used and was most commonly indicated for upper gastrointestinal bleeding. The most common prescribing and administration error were no indication and missed dose error, respectively. Potential drug-drug interactions were also observed and interactions with ferrous sulfate was most commonly observed. Inappropriate utilization cost of IV omeprazole amounted to PhP 8,758.80. There was a discrepancy of PhP 14,273.60 between the administered and appropriately prescribed IV omeprazole. The study revealed high prevalence of inappropriate prescribing as well as drug therapy problems associated with the use of IV PPIs which reflects the global trends of intravenous proton pump inhibitor use in the hospital setting.